Juridical Study On Capital Market Crimes In The Indonesia Stock Exchange According To Law No. 8 Year 1995 About Capital Market - Witiya (Journal of Law Science, 2021)
The Capital Market has a very important role in the current era of economic modernization which is balanced with the Capital Market crimes that occur so that further discussion is needed. The problems raised in this thesis are the scope of capital market crimes and their legal basis, how to deal with capital market crimes and the parties authorized to handle them, and cases of violations in the Capital Market and how the legal force of verdicts is on the settlement of violation cases in the Capital Market. The research method used in writing this thesis is a normative research method, namely by studying literature by obtaining materials from books, laws and regulations, and electronic media. The results of this study indicate that there are four categories of capital market crimes that occur on the Indonesia Stock Exchange, namely fraud, market manipulation, insider trading and misleading information. All decisions of Bapepam based on Law No. 8 of 1995 are weak because they are only limited to administrative sanctions.